Women's Language Features of Dalia Mogahed at Tedtalks in View of Islamic Speaking Ethics - Dini Aulia Rahmah; Zuliati Rohmah; A. Dzo’ul Milal (Universitas Brawijaya, 2020)
This paper investigates women's language features and their functions in the speech by Dalia Mogahed, a Muslim woman, at TEDTalks based on Lakoff’s and Pearson's theories. The researchers deal with Dalia's utterances focusing on the women’s language functions in view of speaking ethics in Islam. This study aims (1) to analyze the functions of women’s language features, and (2) to examine their relationship with the Islamic speaking ethics used by Dalia Mogahed. The researchers use a qualitative approach in conducting this study. The findings demonstrate that Dalia applies some women's language features and functions. Her speech contains women’s language features, i.e. lexical hedges, rising intonation on declarative, empty adjectives, intensifiers, hypercorrect grammar, avoidance of strong swear words, and emphatic stress. They are used for the functions of starting a discussion, expressing feelings, and softening utterances in compliance with Islamic speaking ethics. Consistent with the speaker’s characteristics and constrained by the situational contexts, the speech by Delia is sublime, straightforward and uncomplicated, honest and truthful, effective, gentle, and polite. In conclusion, language use is constrained by various contexts including genders, communicative purposes, and personal characteristics.